Lifestyle, course of COVID-19, and risk of Long-COVID in non-hospitalized patients - Pływaczewska-Jakubowska, Magdalena; Chudzik, Michał; Babicki, Mateusz; Kapusta, Joanna; Jankowski, Piotr (Frontiers in Medicine, 2022)
Introduction: The coronavirus disease (COVID) 2019 pandemic remains a great challenge for the healthcare systems. The widely reported prolonged signs and symptoms resulting from SARS-CoV-2 infection (Long-COVID) require the medical care. The aim the study was to assess factors, including lifestyle variables, related to the course of COVID-19 infection and to assess their impact on prolonged symptoms in non-hospitalized patients with COVID-19. Methods: A total of 1847 (637 males and 1210 females) non-hospitalized participants of the STOP-COVID registry of the PoLoCOV-Study who, following a COVID-19, underwent check-up examinations at the cardiology outpatient clinic were included in the analysis. Results: The study participants (median age 51 [41-62] years) were evaluated 13.4 (8.4-23.6) weeks following COVID-19 diagnosis. Female sex (OR 1.46 [95% CI 1.19-1.78]), body mass index (per 1 kg/m2: 1.02 [1.00-1.04]), hypertension (1.39 [1.07-1.81]), asthma (1.55 [1.06-2.27]), stress or overworking (1.54 [1.25-1.90]), and nightshifts (1.51 [1.06-2.14]) were independently related to the severity of symptoms during acute phase of the COVID-19 infection. The Long-COVID syndrome was independently related to the female sex (1.42 [1.13-1.79]), history of myocardial infarction (2.57 [1.04-6.32]), asthma (1.56 [1.01-2.41]), and severe course of the acute phase of the COVID-19 infection (2.27 [1.82-2.83]). Conclusion: Female sex, body mass index, asthma, hypertension, nightshifts, and stress or overworking are significantly related to the severity of acute phase of the COVID-19 infection, while female sex, asthma, myocardial infarction in the history, and the severity of symptoms in the acute phase of COVID-19 are predictors of Long-COVID in non-hospitalized patients. We did not find an independent relation between Long-COVID and the studied lifestyle factors.